Functional capacity, exercise tolerance, muscle strength, hang grip, and quality of life in patients with COVID-19. A cross-sectional study - Alshammari, Maha; Shanb, Alsayed; Alsubaiei , Mohammed; Ahsan, Mohammad; Shanb , Belal (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: The COVID-19 pandemic has posed significant challenges to global health, affecting millions of individuals worldwide. This study aims to investigate the impacts of COVID-19 with moderate severity on functional capacity, exercise tolerance, isometric muscle strength, hand grip, and quality of life. Methods: Ninety-six participants (48 with COVID-19, 48 without COVID-19) were recruited in this cross-sectional study. The effects on functional capacity, exercise-tolerance, isometric muscle power, hand grip, and quality of life were measured. The Mann-Whitney test was employed to compare the significant differences between the COVID-19 and matched groups. The Spearman correlation was used to determine the relationships among outcome measures. Results: The mean values of functional capacity, isometric muscle power, hand grip, and quality of life were significantly reduced in patients with moderate COVID-19 compared to their matched counterparts (p<0.05), except for exercise tolerance (p>0.05). Positive relationships were detected between exercise tolerance, strength of the hand grip, and knee extensors; distance of the 6-minute walk test and exercise tolerance, strength of the hand grip, and knee extensors (p=<0.001). Conclusions: Moderate-severity COVID-19 patients exhibit impairments in functional capacity, exercise tolerance, isometric muscle strength, hand grip strength, and quality of life. Exercise tolerance correlated positively with the 6-minute walk test, hand grip strength, and knee extensor strength.